Mental health care and delivery system at Temeke hospital in Dar es Salaam, Tanzania - Ambikile, Joel Seme (BMC Psychiatry, 2017)
BACKGROUND: Low and middle income countries face many challenges in meeting mental health needs in their regions. Treatment of patients with mental disorders is inadequate in most of these countries and majority of individuals with severe mental disorders remain untreated. The bad news is that mental health problems in these countries are on the rise due to socioeconomic challenges being faced. Regardless of guidelines and directives provided by WHO for organizing mental health services, these countries continue to face many challenges in the effort to cater for mental health needs. Such challenges include lack of human resource for mental health especially at primary health care level, inadequate training of human resource for mental health, misplacement of human resource for mental health, lack of drugs, wrong priorities, problematic insurance coverage for mental disorders, and stigma. This study aimed at exploring mental health care and delivery system at Temeke district hospital, and how services were organized to meet the increasing mental health needs of its population. METHODS: A qualitative study was conducted at Temeke hospital in Dar es Salaam, involving 7 in-depth interviews with mental health care providers, 7 in-depth interviews with mentally ill patients, and 2 focus group discussions with caregivers. A convenient sampling procedure was used to select participants for the study. All interviews were audio-recorded in Kiswahili and transcribed. A qualitative Content Analysis was used to analyze data after translation with the aid of Nvivo 10 software. RESULTS: Three main themes were identified. These were resource challenges, environmental/system challenges, and satisfaction with mental health services. Temeke health facility faced resource and environmental/system challenges, and there were mixed feelings on satisfaction with services. Funding and priority issues were found to mainly affect delivery of appropriate services to clients. CONCLUSION: Health facilities that provide mental health services in the community need to be well equipped with necessary resources to meet the vast needs of people they serve. Having a political will, improving the health systems governance for mental health, and priority setting, are necessary to address the challenges experienced in the delivery of mental health services.